Efeito da variação de frequência e duração do estímulo no registro do P300 e MMN - Gução, Ana Cláudia Bianco [UNESP] (2014)
Introduction: The Cognitive Potential (CP) test refers to the picking up of specific electric events that evoke sensory responses of the brain from external stimuli. CPs are composed of N1, P2, N2, P3 and MMN components, which reflect the integrity and neuromaturational state of the auditory pathway in children, specifically auditory cortical abilities such as attention, discrimination, memory and brain integrity. This test, applied in children with typical development, is of great value, since these normative data will assist in understanding alterations in children's language and learning linked to attention deficits and auditory memory and cognition. Objective: To investigate the effect of frequency variation and duration on Cognitive Potentials (CPs) in children with typical development. Materials and Methods: 50 subjects (27 males and 23 females) aged 8-12 years and 11 months who attended private and public schools in Marilia and had good academic performance. These individuals were divided into two groups according to age: one group with 8 to10 years 11 months children and the other with 11 to12 years 11 months children. As inclusion criteria, we admitted subjects without neurological, psychiatric or motor impairments, according to the history answered by parents and hearing acuity within normal standards according to audiological evaluation. Cognitive potential, P300 and its other components and MMN were performed, differing in frequency and duration, measured at right and left. Data analysis was carried out using descriptive statistics of mean, standard deviation, minimum and maximum. Following, comparative analyzes were made between the variations of frequency versus duration for each component using the Student T Test as well as correlation of frequency and duration measures through Pearson Correlation Test for P300 and its other components and MMN. Results: It was observed that the discrimination of frequency produced alteration...